LECTOR a technique for leakage reduction in CMOS circuits. - Hanchate, N. (IEEE Transactions on VLSI systems)
In CMOS circuits, the reduction of the threshold voltage due to voltage scaling leads to increase in subthreshold leakage current and hence static power dissipation. We propose a novel technique called LECTOR for designing CMOS gates which significantly cuts down the leakage current without increasing the dynamic power dissipation. In the proposed technique, we introduce two leakage control transistors (a p-type and a n-type) within the logic gate for which the gate terminal of each leakage control transistor (LCT) is controlled by the source of the other. In this arrangement, one of the LCTs is always "near its cutoff voltage" for any input combination. This increases the resistance of the path from Vdd to ground, leading to significant decrease in leakage currents. The gate-level netlist of the given circuit is first converted into a static CMOS complex gate implementation and then LCTs are introduced to obtain a leakage-controlled circuit. The significant feature of LECTOR is that it works effectively in both active and idle states of the circuit, resulting in better leakage reduction compared to other techniques. Further, the proposed technique overcomes the limitations posed by other existing methods for leakage reduction. Experimental results indicate an average leakage reduction of 79.4% for MCNC'91 benchmark circuits.